Evaluation of indicators of goniometry of the ankle joint in the complex rehabilitation of athletes with peroneal tendinopathy - A. D. Repetyuk; E. E. Achkasov; A. P. Sereda; N. R. Zhestyankin (National Electronic Information Consortium (NEICON), 2022)
The study reflects the results of comprehensive rehabilitation of professional athletes with fibular tendinopathy. The effectiveness was evaluated based on the indicators of goniometry of the ankle joint at different stages of the rehabilitation process.Objective. To evaluate the effectiveness of the developed comprehensive program of physical rehabilitation with tendinopathy of the fibular tendons.Materials and methods. The study involved 60 professional male athletes with the diagnosis of "fibular tendinopathy" established by ultrasound examination. All patients were randomly divided into two equal groups of 30 people. Group I patients, in addition to the main ones, were assigned specially designed exercises for balance, balance and proprioceptive sensitivity on the Biodex Balance System (BBS) biofeedback system (Biodex Medical Systems, Inc. New York, USA), as well as balancing disksResults. The percentage of reduction in the total amplitude of movement in the ankle joint, that is, its deficiency, statistically significantly differed between the groups. Thus, at the time of examination before the start of treatment, the total amplitude deficit in group I patients was 13.2°, and in group II - 14.0°. At week 6 after the start of treatment, this indicator improved in group I patients and amounted to 3.8°, and in group II - 12.2°.